2012
DOI: 10.1016/j.ssc.2012.01.047
|View full text |Cite
|
Sign up to set email alerts
|

Quenching of the DOS beats in a two-dimensional electron gas in tilted magnetic fields

Abstract: A two-dimensional electron gas exposed to a tilted magnetic field is considered with the Rashba spin-orbit interaction and the Zeeman effect. An exact solution for the eigenvalues was obtained assuming that two opposite spin states of adjacent Landau levels have equal probability. No crossings between adjacent eigenenergies were observed, for the tilt angles studied here (θ ≤ 80 • ), unlike in the perpendicular-magnetic-field case. The absence of crossings lead to quenched beating structures in the oscillation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Moreover, only at these regions did we also observe the crossings which is indicative of beats and crossings being concomitant. Since the beats are due to the spin splitting induced by the Rashba SOI and crossings are found in the case of zero tilt [4,22] but are not found for θ < 80 • [4], we deduce that the magnetic field's tilt relative to the 2DEG plane shifts the spin splitting-induced crossings to large angles as observed in this paper.…”
Section: Density Of Statessupporting
confidence: 62%
See 3 more Smart Citations
“…Moreover, only at these regions did we also observe the crossings which is indicative of beats and crossings being concomitant. Since the beats are due to the spin splitting induced by the Rashba SOI and crossings are found in the case of zero tilt [4,22] but are not found for θ < 80 • [4], we deduce that the magnetic field's tilt relative to the 2DEG plane shifts the spin splitting-induced crossings to large angles as observed in this paper.…”
Section: Density Of Statessupporting
confidence: 62%
“…Not only is the Rashba SOI linked with the beats in these Shubnikov-de Haas (SdH) oscillations but it also gives way to a direction-dependent energy spectrum [15]. The authors of this present paper have previously shown that when both Rashba and Zeeman interactions are taken into account there are no beating patterns in the density of states of the 2DEG for θ ≤ 80 • [4]. The authors observed that depending on the intensity of the applied magnetic field B, the Rashba SOI and Zeeman term signatures can be distinguished [5].…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…The density of delocalized states thus remains sharp about the band centers, which causes several thermodynamic and transport quantities of the 2D electron gas to exhibit pronounced changes as the Fermi level jumps discontinuously between delocalized band gaps [20][21][22][23][24][25]. Indeed, experimental observations of the Shubnikov-de Haas effect and de Haas-van Alphen effect have been used to obtain the value of the Rashba parameter [21,24,[26][27][28][29][30][31][32][33][34][35]. The second objective of this work is to show that similar integer effects exist in the total spinorbit entanglement entropy originating from the Rashba interaction (section 3).…”
Section: Introductionmentioning
confidence: 99%